Study on the Result of Unstable Intertrochanteric Fracture Treated by Trochanter Stabilizing Plate (TSP) in 65 Years and Above Old Age Group (Green Life Medical College Journal, 2026)
Introduction: The management of unstable intertrochanteric fractures, particularly in individuals aged 65 and older, presents a significant challenge for orthopedic surgeons. A sliding screw device offers numerous benefits; however, its application in unstable trochanteric fractures has been linked to issues such as collapse and medialization of the femoral shaft. The trochanteric stabilizing plate (TSP), an add-on plate that extends proximally from the side plate, providing a lateral support to the greater trochanter. This study aimed to assess the outcomes of selected unstable intertrochanteric fractures classified as AO type 31-A2.2, 2.3, and 3.3, which were treated with TSP in patients aged 65 years and older.Methods: This was a prospective observational study, carried out in National institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka from July 2017 to June 2018. After fulfilling inclusion and exclusion criteria a total of 10 cases treated with TSP superimposed on the regular DHS analysed.Results: Out of 10 cases, 6 were female and 4 were male. Mean age 74.20 years (SD 7.64). Sedentary working job were the prominent occupation with 90% cases. Left side was involved in 60% cases. Maximum of 50% cases had ASA stage II. Abbreviated mental test score mean was 8.80 with SD 1.13. Mean interval between injury & operation was 7.10 days (SD 2.37). Mean operation duration was 94.50 minutes (SD 14.23) and hospital duration was 13.40 days with SD 2.98. Lateralization of the greater trochanter and lag screw cut-out was successfully prevented in all fractures. Average lag screw sliding was 5.90 mm with SD 2.84. All fractures had healed within 18 weeks. More than 10° varus deformity observed in one case, but functional outcome was fair. One patient had persistent hip pain needed re-operation, followed by full gain of function. One patient had superficial wound infection, which was improved conservatively. One patient died of unrelated to operation after radiological union. Pre-fracture Parker Mobility Score 7.60 with SD 0.96 and on last follow-up 7.10 with SD 1.66. Hip functional results were satisfactory in 80% of patients and unsatisfactory in 20% according to the Salvati-Wilson score.Conclusion: In selected unstable intertrochanteric fractures characterized by a small or absent lateral cortical buttress in individuals aged 65 years and older, incorporating a TSP with the DHS provides effective support for the unstable greater trochanter fragment. This addition can help avert lateralization, screw cut-out, and limb shortening, thereby enhancing surgical outcomes.Journal of Green Life Med. Col. 2026; 11(1): 3-12